On the Current State of Ground-based Transmission Spectroscopy of Planet Atmospheres. Issue Volume 8:Issue S293(2012) (29th April 2014) - Nortmann, Lisa; Dreizler, Stefan; Bean, Jacob
Abstract: In response to the large number of exoplanet detections, the characterization of these planets has become a major focus of exoplanet science. Transiting planets are of particular interest as they allow us to investigate the transmission of their atmospheres. Our group uses ground-based facilities like the ESO/VLT to probe the atmosphere of hot Jupiters with the technique of spectrophotometry. In our preliminary results for the hot Jupiters WASP-17b and WASP-31b we find the reachable precision to be limited by instrumental systematic noise rather than photon noise. We discuss the source of the noise and suggest two approaches to correct it.